Attitudes of full-time and adjunct electronics instructors in Texas community colleges toward technical skill standards - Davis, Jason Lee, author; Jansen, Duane G., advisor; De Miranda, Michael, committee member; Gloeckner, Gene W., committee member; Davies, Timothy Gray, committee member (Colorado State University. Libraries, 2002)
There is a perceived problem that a gap exists between industry and education in regards to skill standards for electronic technician training. Additionally, there is a perception of a problem arising from variance in attitudes between full-time and adjunct instructors. The purpose of the dissertation was to determine the attitudes of community/junior college electronics instructors (both full-time and part-time) toward validated skill standards in electronic technology. These standards, used for comparison in this dissertation, were developed and validated in a national level study conducted by the Electronic Industries Association and were titled Raising the Standard-Electronics Technician Skills for Today and Tomorrow. In this dissertation study, electronic technology instructors were asked to express their level of agreement regarding the essential knowledge and skill standards developed in the Raising the Standard project. The null hypothesis for the dissertation was that no significant differences existed between the attitudes of electronics instructors toward validated standards developed in the Raising the Standard project Fifty-seven electronic technology instructors from 15 Texas community/junior colleges participated in the study. Profiles of electronic technology instructors in the sample population were generated from demographic data collected from the participants. The profile of an electronics instructor in the sample population was concluded to be a person over 35 years of age with a Master's degree in an engineering, science, or technology related discipline and at (east one degree in electronics or an electronics related discipline. The participating electronics instructor had more than three years of business or industrial experience and more than two years of teaching experience. An analysis of the data applying Wilks' Lambda in a 2X2 MANOVA revealed no significant differences at the .05 alpha level between or within groups of full-time, adjunct, rural, and urban electronics instructors toward the identified technical skill standards. The null hypothesis that there is no significant difference in the attitudes of electronics instructors in Texas community/junior colleges toward entry-level technical electronics skills identified in Raising the Standard was not rejected.
Keywords: vocational education; community colleges; industrial arts education; community college education